Discharge Planning of Stroke Patient in Regional General Hospital Ungaran - Rosiana Eva Rayanti; Laudri J.L. Yoel (Universitas Respati Yogyakarta, 2020)
In 2011, the prevalence of stroke in Central Java was 0.03%, then increased significantly in 2012, which was 0.07%. In 2012, the prevalence in Semarang city was 11.9%. In 2015, Regional General Hospital Ungaran had 202 stroke cases, and 31 of the patients died. After the patients are hospitalized, they have discharge planning for preparing them to go home. The purpose of this study is tu describe the implementation of discharge planning for stroke patients at the Hospital. This research uses a qualitative method. There are two groups of research participants in this research, which are four nurses and four post-stroke patients. The data collection techniques used semi-structured interviews and observations. The results showed 1) patient's activities change after the stroke experience, caused by the physical weakness and the dietary habit. 2) Nurse educators provide information about the condition and prevention of the disease, which is taking the medication, exercising regularly, and a healthy diet. 3) Criteria for discharged patients based on a doctor visit and normal vital sign ranges of the patient. 4) Discharge planning started when first-time patients were admitted to the hospital until they returned home. 5) Obstacles in the discharge planning process were the patients who did not return home and the unsettled administration dues. The conclusion of this study is the nurse already conducted discharge planning to the stroke patients at the hospital, but nurses need to optimize their role in the implementation of discharge planning